Synthesis of C70-fragment buckybowls bearing alkoxy substituents - Yakiyama, Yumi; Hishikawa, Shota; Sakurai, Hidehiro (Beilstein Journal of Organic Chemistry, 2020)
Buckybowls bearing a C70 fragment having two alkoxy groups were synthesized and their structural and optical properties were investigated by single crystal X-ray analysis and UV–vis spectroscopy. In the synthesis of dioxole derivative 5b, the regioisomer 5c was also produced. The yield of 5c was increased by increasing the reaction temperature, indicating that the rearrangement might involve the equilibrium between the Pd(IV) intermediates through C–H bond activation.
Keywords: buckybowl; C70; rearrangement through C–H bond activation

(untitled) - Wu, Y.-T.; Siegel, J. S. (Chem. Rev., 2006)

(untitled) - Tsefrikas, V. M.; Scott, L. T. (Chem. Rev., 2006)

(untitled) - Amaya, T.; Hirao, T. (Chem. Commun., 2011)

(untitled) - Sygula, A. (Eur. J. Org. Chem., 2011)

(untitled) - Higashibayashi, S.; Sakurai, H. (Chem. Lett., 2011)

(untitled) - Schmidt, B. M.; Lentz, D. (Chem. Lett., 2014)

(untitled) - Saito, M.; Shinokubo, H.; Sakurai, H. (Mater. Chem. Front., 2018)

(untitled) - Nestoros, E.; Stuparu, M. C. (Chem. Commun., 2018)

(untitled) - Scott, L. T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Jackson, E. A.; Steinberg, B. D.; Bancu, M.; Wakamiya, A.; Scott, L. T. (J. Am. Chem. Soc., 2007)

(untitled) - Amaya, T.; Nakata, T.; Hirao, T. (J. Am. Chem. Soc., 2009)

(untitled) - Wu, T.-C.; Hsin, H.-J.; Kuo, M.-Y.; Li, C.-H.; Wu, Y.-T. (J. Am. Chem. Soc., 2011)

(untitled) - Wu, T.-C.; Chen, M.-K.; Lee, Y.-W.; Kuo, M.-Y.; Wu, Y.-T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Chen, M.-K.; Hsin, H.-J.; Wu, T.-C.; Kang, B.-Y.; Lee, Y.-W.; Kuo, M.-Y.; Wu, Y.-T. (Chem. – Eur. J., 2014)

(untitled) - Amaya, T.; Ito, T.; Hirao, T. (Angew. Chem., Int. Ed., 2015)

(untitled) - Liu, J.; Osella, S.; Ma, J.; Berger, R.; Beljonne, D.; Schollmeyer, D.; Feng, X.; Müllen, K. (J. Am. Chem. Soc., 2016)

(untitled) - Tian, X.; Roch, L. M.; Baldridge, K. K.; Siegel, J. S. (Eur. J. Org. Chem., 2017)

(untitled) - Hishikawa, S.; Okabe, Y.; Tsuruoka, R.; Higashibayashi, S.; Ohtsu, H.; Kawano, M.; Yakiyama, Y.; Sakurai, H. (Chem. Lett., 2017)

(untitled) - Shoji, Y.; Kajitani, T.; Ishiwari, F.; Ding, Q.; Sato, H.; Anetai, H.; Akutagawa, T.; Sakurai, H.; Fukushima, T. (Chem. Sci., 2017)

(untitled) - Bavin, P. M. G. (Can. J. Chem., 1959)

(untitled) - Mota, A. J.; Dedieu, A.; Bour, C.; Suffert, J. (J. Am. Chem. Soc., 2005)

(untitled) - Mota, A. J.; Dedieu, A. (Organometallics, 2006)

(untitled) - Mota, A. J.; Dedieu, A. (J. Org. Chem., 2007)

(untitled) - Misawa, N.; Tsuda, T.; Shintani, R.; Yamashita, K.; Nozaki, K. (Chem. – Asian J., 2018)

(untitled) - Kanagaraj, K.; Lin, K.; Wu, W.; Gao, G.; Zhong, Z.; Su, D.; Yang, C. (Symmetry, 2017)

(untitled) - Haddon, R. C. (J. Am. Chem. Soc., 1987)

RAPID-AUTO (Rigaku Corporation, 2001)

(untitled) - Minor, W.; Cymborowski, M.; Otwinowski, Z.; Chruszcz, M. (Acta Crystallogr., Sect. D: Biol. Crystallogr., 2006)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)

SHELXTL (Bruker AXS Inc., 2012)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)